Accuracy of Asymptotic Standard Errors of the Maximum and Weighted Likelihood Estimators of Proficiency Levels With Short Tests. (March 2014) - Magis, David
The maximum likelihood (ML) and the weighted likelihood (WL) estimators are commonly used to obtain proficiency level estimates with pre-calibrated item parameters. Both estimators have the same asymptotic standard error (ASE) that can be easily derived from the expected information function of the test. However, the accuracy of this asymptotic formula is unclear with short tests when only a few items are administered. The purpose of this paper is to compare the ASE of these estimators with their exact values, evaluated at the proficiency-level estimates. The exact standard error ( SE ) is computed by generating the full exact sample distribution of the estimators, so its practical feasibility is limited to small tests (except under the Rasch model). A simulation study was conducted to compare the ASE and the exact SE of the ML and WL estimators, with the "true" SE (i.e., computed as the exact SE with the true proficiency levels). It is concluded that with small tests, the exact SE s are less biased and return smaller root mean square error values than the asymptotic SE s, while as expected, the two estimators return similar results with longer tests.